HUBUNGAN USIA PERKAWINAN REMAJA DENGAN KEJADIAN ANEMIA PADA TRIMESTER 2 DI PUSKESMAS AMURANG - Agustin Tumangken, Anita; Veronika Widiatrilupi, Raden Maria (NHM PRESS, 2024)
Background: Age of teenage marriage can affect various aspects of health during pregnancy, including the incidence of anemia. Anemia in the second trimester of pregnancy is a significant health problem, potentially affecting the health of the mother and fetus. This study aims to analyze the relationship between age of teenage marriage and the incidence of anemia in the second trimester among pregnant women. Objective: This study aims to evaluate whether there is a significant relationship between age of teenage marriage and the incidence of anemia in the second trimester of pregnancy. Method: This study used a cross-sectional study design involving 16 respondents of pregnant women in the second trimester who experienced anemia. Data were collected through interviews and health checks, and analyzed using statistical tests to determine the relationship between age of teenage marriage and the incidence of anemia. The results of statistical tests are presented with a p-value, which is used to test the research hypothesis. Results: Based on data analysis, a p-value of 0.000 was obtained. These results indicate that the null hypothesis (Ho) which states that there is no relationship between age of teenage marriage and the incidence of anemia in the second trimester is rejected, while the alternative hypothesis (Ha) which states that there is a relationship is accepted. This indicates that there is a significant relationship between age of teenage marriage and the incidence of anemia in the second trimester. Conclusion: This study shows a significant relationship between the age of teenage marriage and the incidence of anemia in the second trimester.